Understanding trauma-impaired executive function and its impacts on homeless adults in the UK: a realist evaluative synthesis protocol - Monique Lhussier; Christina Cooper (BMJ Open)
Introduction Approximately 90% of people with experience of homelessness report adverse childhood experiences, having far-reaching consequences across the life course. Trauma-informed approaches have burgeoned in the last decade; however, biological understandings, including neurological perspectives of the impact of trauma, are typically overlooked. At present, there is little evidence exploring the impacts of executive function (EF) deficits in adulthood as a result of childhood trauma from a lived experience perspective, with none specifically exploring the role these deficits might play in homelessness.Methods and analysis The proposed research takes a realist evaluative synthesis approach combining evidence from the extant literature with qualitative data from professionals involved in the delivery of services to support people with experience of homelessness (n=15–20) and people with experience of homelessness who have previously engaged with services (n=15–20).A combination of keywords (Adverse childhood experiences, executive function, social functioning and complex needs) and their synonyms will be used to search databases MEDLINE, PubMed, SCOPUS, Web of Science and CINAHL. Data analysis will follow a realist logic, developing and refining programme theories. An iterative and cyclical approach to data analysis and evidence synthesis will be taken until the aims of the research have been met.Ethics and dissemination Findings from this study will contribute to new understandings of the pathways into and out of homelessness through the lens of EF. Findings will contribute to the development of a trauma-informed care toolkit for service providers. Findings will be disseminated via coproductive workshops, conferences and peer-reviewed publications.This study has received ethical approval from the ethics committee at Northumbria University.